2017
DOI: 10.1002/2017gl073869
|View full text |Cite
|
Sign up to set email alerts
|

Longwave emission trends over Africa and implications for Atlantic hurricanes

Abstract: The latitudinal gradient of outgoing longwave radiation (OLR) over Africa is a skillful and physically based predictor of seasonal Atlantic hurricane activity. The African OLR gradient is observed to have strengthened during the satellite era, as predicted by state‐of‐the‐art global climate models (GCMs) in response to greenhouse gas forcing. Prior to the satellite era and the U.S. and European clean air acts, the African OLR gradient weakened due to aerosol forcing of the opposite sign. GCMs predict a continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Ting et al (2015) concluded that aerosols are more effective than greenhouse gases in modulating Atlantic PI changes and that the PI increases over the last 30 years have been dominated by multidecadal natural variability. Zhang et al (2017) used statistical methods to infer an impact of aerosol forcing on Atlantic TC activity via its influence on gradients of African outgoing longwave radiation. Balaguru et al (2018) tentatively attributed increases in Atlantic hurricane rapid intensification during 1986-2015 to natural variability, though not ruling out anthropogenic forcing.…”
Section: Case Studies -Assessment Of De-tection and Attributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ting et al (2015) concluded that aerosols are more effective than greenhouse gases in modulating Atlantic PI changes and that the PI increases over the last 30 years have been dominated by multidecadal natural variability. Zhang et al (2017) used statistical methods to infer an impact of aerosol forcing on Atlantic TC activity via its influence on gradients of African outgoing longwave radiation. Balaguru et al (2018) tentatively attributed increases in Atlantic hurricane rapid intensification during 1986-2015 to natural variability, though not ruling out anthropogenic forcing.…”
Section: Case Studies -Assessment Of De-tection and Attributionmentioning
confidence: 99%
“…1c) show a nominally negative decline, although the trend over 1900-2017 is not statistically significant . Hurricane Harvey's U.S. landfall in 2017 ended an 11-yr "drought" of majorhurricane U.S. landfalls (Kossin et al 2017), which had been tentatively attributed to natural variability (Hall and Hereid 2015). Hart et al (2016) discussed several limitations of focusing on such an index of major-hurricane U.S. landfalls, noting the arbitrariness of several aspects of the index.…”
Section: Case Studies -Assessment Of De-tection and Attributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Atlantic Niño is associated with prominent climate anomalies across the tropical Atlantic and has far-reaching impacts on climate in remote regions [3][4][5][6] . For instance, the Atlantic Niño enhances seasonal rainfall over South America and Africa 7,8 ; it can also affect the African Easterly Jet 9 , which can subsequently influence Atlantic hurricanes 10,11 . It has been suggested that the Atlantic Niño may strengthen the Pacific Walker circulation and lead to La Niña [12][13][14][15] , the negative phase of ENSO.…”
mentioning
confidence: 99%